2021
DOI: 10.20853/35-2-4025
|View full text |Cite
|
Sign up to set email alerts
|

External factors affecting blackboard learning management system adoption by students: Evidence from a historically disadvantaged higher education institution in South Africa

Abstract: Learning Management Systems (LMS) have the ability to transform learning experiences of students in Higher Education Institutions (HEI). In addition to the developmental benefits, LMS assist teaching and learning during student unrests, a common feature in historically disadvantaged institutions in South Africa. Regardless of the benefits of LMS platforms such as Blackboard, the utilisation by university students at the institution under study has been very low.Applying cross sectional electronic survey, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The evaluation in these cases becomes more complex, mainly when it is used in long self-reporting surveys or when it comes to quantifying all these included factors. Recent studies assure the positive effect of self-efficacy on perceived students' behavior in using E-learning [22,37], which are consistent with the obtained results in our research. Here the results are additionally compared with actual usage figures.…”
Section: Discussionsupporting
confidence: 93%
“…The evaluation in these cases becomes more complex, mainly when it is used in long self-reporting surveys or when it comes to quantifying all these included factors. Recent studies assure the positive effect of self-efficacy on perceived students' behavior in using E-learning [22,37], which are consistent with the obtained results in our research. Here the results are additionally compared with actual usage figures.…”
Section: Discussionsupporting
confidence: 93%
“…Students are of the opinion that learning material, in particular, audio-video files act as a guide to delve deeper into building their own knowledge (Conole et al 2004, 24). Matarirano et al (2021) too found low utilisation of the LMS by students at Walter Sisulu University. Their findings show that students preferred visual material.…”
Section: Discussionmentioning
confidence: 90%
“…As teaching and learning shifts from face-to-face to totally online, having an easy-to-use Blackboard that allows lecturers and students to learn independently will undoubtedly result in more engaging teaching experiences and enhanced teaching and learning ( Han and Shin, 2016 ). It is vital for education, particularly for students from underprivileged backgrounds, to develop ways to make the use of technology fun in order to fully benefit from learning management systems such as Blackboard ( Matarirano et al, 2021 ). As a result, this research shows that using Blackboard as an online LMS can have a favorable impact on lecturers’ performance during the epidemic, resulting in more engaging teaching experiences.…”
Section: Discussionmentioning
confidence: 99%